MENINGKATKAN PROFESIONALISME GURU DALAM KEGIATAN BELAJAR MENGAJAR MELALUI PENYELENGGARAAN SCHOOL BASED INSET DI SD NEGERI LEME-LEME KECAMATAN BUKO KABUPATEN BANGGAI KEPULAUAN SEMESTER GANJIL TAHUN PELAJARAN 2021/2022: SD NEGERI LEME-LEME KECAMATAN BUKO KABUPATEN BANGGAI KEPULAUAN - YORIM MUANI (Dewan Pendidikan Bondowoso, 2022)
Problems in the implementation of teaching in schools will always be faced with various kinds of teacher abilities, both new teachers, juniors and seniors. As a principal, you should look for alternatives in an effort to improve teacher professionalism. In order for us to better understand the personal duties of the school, be it principals, teachers or administrative staff, we should pay attention to: Professional duties, human duties, and social duties of the personnel, considering that teachers are directly involved in teaching and learning activities and have a great influence on the teaching and learning activities. school success. The research was carried out at SD Negeri Leme-leme, Buko District, Banggai Islands, Odd Semester for the 2021/2022 Academic Year. In this study, it was concluded that: (a) School Based Inset at SD Negeri Leme-Leme, Buko District, Banggai Islands Regency became a very important instrument to advance the teaching system in the classroom. (b) School Based Inset has an important role in efforts to improve the professionalism of teachers in teaching and learning activities, because it makes teachers more advanced, insightful in science and technology that is more modern.